Lipases and lipid droplet-associated protein expression in subcutaneous white adipose tissue of cachectic patients with cancer - Silvério, Renata; Lira, Fábio S. [UNESP]; Oyama, Lila M.; Oller Do Nascimento, Cláudia M.; Otoch, José P.; Alcântara, Paulo S. M.; Batista, Miguel L.; Seelaender, Marília (Springer Nature, 2017)
Background: Cancer cachexia is a multifactorial metabolic syndrome characterized by marked loss of adipose tissue and skeletal muscle. Fat loss from adipose tissue in cancer cachexia is partly the result of increased lipolysis. Despite the growing amount of studies focused on elucidating the mechanisms through which lipolysis-related proteins regulate the lipolytic process, there are scarce data concerning that profile in the adipose tissue of cancer cachectic patients. Considering its fundamental importance, it was our main purpose to characterize the expression of the lipolysis-related proteins in the white adipose tissue of cachectic cancer patients. Methods: Patients from the University Hospital were divided into three groups: control, cancer cachexia (CC), and weight-stable cancer patients (WSC). To gain greater insight into adipose tissue wasting during cancer cachexia progression, we have also analyzed an experimental model of cachexia (Walker 256 carcinosarcoma). Animals were divided into: control, intermediate cachexia (IC) and terminal cachexia (TC). Subcutaneous white adipose tissue of patients and epidydimal white adipose tissue of animals were investigated regarding molecular aspects by determining the protein content and gene expression of hormone-sensitive lipase (HSL), adipose triglyceride lipase (ATGL), comparative gene identification-58 (CGI-58), perilipin 1, leptin, adiponectin, visfatin, and tumour necrosis factor alpha (TNF-alpha). Results: We found augmented lipolysis in CC associated with increased HSL expression, as well as upregulation of ATGL expression and reduction in perilipin 1 content. In IC, there was an imbalance in the secretion of pro- and anti-inflammatory factors. The alterations at the end-stage of cachexia were even more profound, and there was a reduction in the expression of almost all proteins analyzed in the animals. Conclusions: Our findings show that cachexia induces important morphological, molecular, and humoral alterations in the white adipose tissue, which are specific to the stage of the syndrome.